Prognostic Value of Procalcitonin in Febrile People Living with Human Immunodeficiency Virus (PLWH) Admitted to the Emergency Department - Luigi Celani; Luigi Carbone; Francesco Ceppa; Andrea Piccioni; Davide Antonio Della Polla; Marta Chiuchiarelli; Antonella Cingolani; Giuseppe De Matteis; Rita Murri; Antonio Gasbarrini; Francesco Franceschi; Marcello Covino (Medicina)
Background and Objectives: The management of HIV patients presenting with fever in the Emergency Department (ED) remains a challenging clinical scenario. Accurate risk stratification and prognostic indicators are crucial for timely intervention and improved patient outcomes. Procalcitonin (PCT) has emerged as a promising biomarker for assessing the severity and prognosis of various infectious diseases. The study aimed to evaluate the prognostic value of procalcitonin (PCT) in HIV patients admitted to the Emergency Department for clinical suspicion of infection and assess its association with in-hospital mortality. Methods: A retrospective analysis was conducted on febrile HIV-positive patients admitted to the Emergency Department. Clinical data were collected from 2018 to 2022. Patients were categorized based on PCT levels (>0.5 ng/dL), clinical findings, comorbidities, and viro-immunological status. Results: We investigated data from 289 HIV-positive patients (74% male). The median age of the sample was 54 years [IQR: 42–62], 100 (35%) patients presented detectable viremia, and the median value of CD4+ T lymphocytes was 358 [IQR: 104–531]. Elevated PCT levels (≥0.5 ng/dL) were detected in 69 (23.8%) patients. A significant association was observed between elevated PCT and increased mortality risk (p < 0.05). The mortality rate among patients with detectable HIV viremia was higher compared to those with undetectable viremia (p = 0.02). Moreover, deceased patients had statistically lower CD4+ values compared to survivors (61 [IQR: 14–186] vs. 370 [IQR: 136–548], p < 0.001). Conclusions: In febrile HIV patients admitted to the Emergency Department, elevated procalcitonin levels, low CD4+, and detectable viremia are associated with an increased risk of in-hospital mortality.